Saxitoxin Exposure Confirmed by Human Urine and Food Analysis. Issue 7 (25th May 2018) - Coleman, R M; Ojeda-Torres, G; Bragg, W; Fearey, D; McKinney, P; Castrodale, L; Verbrugge, D; Stryker, K; DeHart, E; Cooper, M; Hamelin, E; Thomas, J; et al.
Abstract: A case of an elderly female with suspected paralytic shellfish poisoning (PSP) is presented. The patient shared a meal of recreationally-harvested shellfish with her family and soon began to experience nausea and weakness. She was taken to the local emergency department and then transported to a larger hospital in Anchorage where she was admitted to the intensive care unit with respiratory depression and shock. Her condition improved, and she was discharged from the hospital 6 days later. No others who shared the meal reported symptoms of PSP. A clam remaining from the meal was collected and analyzed for paralytic shellfish toxins (PST) by the Alaska Department of Environmental Conservation Environmental Health Laboratory; the clam tested positive for saxitoxin (STX; 277 μg/100 g), neosaxitoxin (NEO; 309 μg/100 g), multiple gonyautoxins (GTX; 576–2490 μg/100 g), decarbamoyl congeners (7.52–11.3 μg/100 g) and C-toxins (10.8–221 μg/100 g) using high-pressure liquid chromatography with post-column oxidation (AOAC Method 2011.02). Urine from the patient was submitted to Centers for Disease Control for analysis of selected PSTs and creatinine. STX (64.0 μg/g-creatinine), NEO (60.0 μg/g-creatinine) and GTX1–4 (492–4780 μg/g-creatinine) were identified in the urine using online solid phase extraction with HPLC and tandem mass spectrometry. This was the first time GTX were identified in urine of a PSP case from Alaska, highlighting the need to include all STX congeners in testing to protect the public's health through a better understand of PST toxicity, monitoring and prevention of exposures.